Plasminogen–Plasmin System in the Pathogenesis and Treatment of Lung and Pleural Injury - Tucker, Torry; Idell, Steven (Seminars in Thrombosis and Hemostasis, 2013)
Lung and pleural injuries are characterized by inflammation, fibrinous transitional matrix deposition, and ultimate scarification. The accumulation of extravascular fibrin is due to concurrently increased local coagulation and decreased fibrinolysis, the latter mainly as a result of increased plasminogen activator inhibitor-1 (PAI-1) expression. Therapeutic targeting of disordered fibrin turnover has long been used for the treatment of pleural disease. Intrapleural fibrinolytic therapy has been found to be variably effective in clinical trials, which likely reflects empiric dosing that does not account for the wide variation in pleural fluid PAI-1 levels in individual patients. The incidence of empyema is increasing, providing a strong rationale to identify more effective, nonsurgical treatment to improve pleural drainage and patient outcomes. Therapeutics designed to resist inhibition by PAI-1 are in development for the treatment of pleural loculation and impaired drainage. The efficacy and safety of these strategies remains to be proven in clinical trial testing. Fibrinolytic therapy administered via the airway has also been proposed for the treatment of acute lung injury, but this approach has not been rigorously validated and is not part of routine clinical management at this time. Challenges to airway delivery of fibrinolysins relate to bioavailability, distribution, and dosing of the interventional agents.
Keywords: pleura; lung; injury and fibrinolysis; fibrinolytic therapy; plasminogen activator inhibitor-1